(untitled) (MATEMATIKA, 2013)
The main aim of this paper is to obtain some characterizations of piprenormal spaces by using the notion of pi-generalized closed sets. Also, by using these characterizations we establish various preservation theorems of pi-prenormality under continuous and some generalized sense of continuous mappings. We give some characterizations of almost preregular spaces and present some relationships between prenormality and almost preregularity. Keywords: closed domain; p-closed; almost p-regular; p3-paracompact. 2010 Mathematics Subject Classification: 54D15; 54B10; 54D10; 54D70